Multidimensional Scaling: Sustainability of Arabika Coffee Agro-Tourism in Kabupaten Bangli Bali - YUDHARI, I Dewa Ayu Sri; DARWANTO, Dwidjono Hadi; WALUYATI, Lestari Rahayu; MULYO, Jangkung Handoyo (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.11.6(46).16, 2020)
One of the world tourism destinations recognized as Unesco Global Geopark in Bali is Kabupaten Bangli. The main attraction of agriculture in Kabupaten Bangli is Kintamani coffee agrotourism with a beautiful panoramic view of coffee, safe tracking routes for tourists, strategic location, and producing special Arabica Coffee products making Bangli an agricultural tourism destination worth visiting. The purpose of this study is to look at leveraging factors and assess the status of agro-tourism sustainability in terms of four dimensions of sustainability, namely the economic, socio-cultural, environmental and institutional dimensions for the development of Arabica coffee agro-tourism. The results of the evaluation of the 4 dimensions of sustainability indicate that the environmental dimension gets the lowest value. This is because environmental conditions are very vulnerable to land conversion in the future. If agro-tourism cannot provide benefits and economic improvement for the surrounding community, farmers will divert coffee plants to other plants that are more economically profitable. A regulation or local government policy needs to be made in preventing land conversion in the Arabica coffee agro tourism area of Kabupaten Bangli.